Physics I for dummies - Holzner, Steven (Hoboken, NJ : Wiley Publishing, Inc., 2011)
Overview: The fun and easy way to get up to speed on the basic concepts of physics For high school and undergraduate students alike, physics classes are recommended or required courses for a wide variety of majors, and continue to be a challenging and often confusing course. Physics I For Dummies tracks specifically to an introductory course and, keeping with the traditionally easy-to-follow Dummies style, teaches you the basic principles and formulas in a clear and concise manner, proving that you don't have to be Einstein to understand physics!: Explains the basic principles in a simple, clear, and entertaining fashion; New edition includes updated examples and explanations, as well as the newest discoveries in the field; Contains the newest teaching techniques; If just thinking about the laws of physics makes your head spin, this hands-on, friendly guide gets you out of the black hole and sheds light on this often-intimidating subject.
Includes index.
Keywords: Physics; Physics